Inhibitive Determination of Hg(II) in Aqueous Solution Using Urease Amperometric Biosensor - Dhony Hermanto; Bambang Kuswandi; Dwi Siswanta; Mudasir Mudasir (Indonesian Journal of Chemistry, 2019)
An amperometric biosensor for the indirect determination of Hg(II) has been developed based on inhibition of urease (EC 3.5.1.5) immobilized into alginate–chitosan polyelectrolyte complexes membrane. The biosensor response was monitored by following the reduction peak of hydrolyzed urea at around -0.15 V. The amperometric biosensor has a dynamic range 40–90 ppb Hg(II) with limit of detection of 66.45 ppb toward Hg(II) ions, repeatability (CV) value of 0.86% and only Ag(I) as the main potential interference. The sensor shows a stable and reproducible response for more than 2 weeks when it stored dry at 4 °C. The analytical results of Hg(II)-spiked water sample showed a good agreement with those obtained by atomic absorption spectrometry method, suggesting that the developed method may be applied in the determination of Hg(II) in the water samples.